2018
DOI: 10.1104/pp.18.00292
|View full text |Cite|
|
Sign up to set email alerts
|

The NAC Transcription Factor SlNAP2 Regulates Leaf Senescence and Fruit Yield in Tomato

Abstract: Leaf senescence is an essential physiological process in plants that supports the recycling of nitrogen and other nutrients to support the growth of developing organs, including young leaves, seeds, and fruits. Thus, the regulation of senescence is crucial for evolutionary success in wild populations and for increasing yield in crops. Here, we describe the influence of a NAC transcription factor, SlNAP2 ( NAC-like, activated by Apetala3/Pistillata), that controls both leaf senescence and fruit yield in tomato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
150
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(158 citation statements)
references
References 65 publications
7
150
1
Order By: Relevance
“…The plant hormone ABA triggers and promotes the senescence process (Cutler et al, 2010). The NAC TFs NAP and NAC2 are well known to be involved in ABA-promoted leaf senescence by regulating the transcription of chlorophyll degradation genes and ABA metabolic genes in Arabidopsis, rice and tomato (Zhang & Gan, 2012;Liang et al, 2014;Yang et al, 2014;Mao et al, 2017;Ma et al, 2018). However, beyond these, there are few reports of regulators in ABA-promoted leaf senescence, and the underlying molecular mechanism of ABA-modulated leaf senescence is unclear.…”
Section: Researchmentioning
confidence: 99%
“…The plant hormone ABA triggers and promotes the senescence process (Cutler et al, 2010). The NAC TFs NAP and NAC2 are well known to be involved in ABA-promoted leaf senescence by regulating the transcription of chlorophyll degradation genes and ABA metabolic genes in Arabidopsis, rice and tomato (Zhang & Gan, 2012;Liang et al, 2014;Yang et al, 2014;Mao et al, 2017;Ma et al, 2018). However, beyond these, there are few reports of regulators in ABA-promoted leaf senescence, and the underlying molecular mechanism of ABA-modulated leaf senescence is unclear.…”
Section: Researchmentioning
confidence: 99%
“…As seen in Figure 6A (and Table S2 is that SlORE1 genes directly control ripening processes in fruits. Similarly, downregulation 433 of NAC transcription factor SlNAP2 expression delays leaf senescence in tomato followed by 434 an increased fruit yield (Ma et al, 2018). SlNAP2 binds to the promoters of several 435 senescence-related genes, including SlSAG113 (Solanum lycopersicum SENESCENCE-436 ASSOCIATED GENE113) and the chlorophyll-degradation genes SlSGR1 (S. lycopersicum 437 senescence-inducible chloroplast stay-green protein 1) and SlPAO (S. lycopersicum 438 pheide a oxygenase).…”
Section: Identification Of Nor Target Genes 297mentioning
confidence: 99%
“…suggesting that it has an important function in controlling ABA homeostasis in senescing 441 tomato leaves (Ma et al, 2018). 442…”
Section: Identification Of Nor Target Genes 297mentioning
confidence: 99%
“…NAC TFs play important regulatory roles in various aspects of plant growth, development, and adaptation to the environment, including in shoot apical meristem formation [5], cell division and expansion [6,7] nutrient remobilization [8], flower formation [9], lateral root development [10,11], leaf senescence [12][13][14][15][16], secondary cell wall biosynthesis [3,[17][18][19][20], fiber development [19,21,22], fruit ripening [23,24], seed development [25], response to pathogen infection [26][27][28][29][30], and abiotic stress tolerance [31][32][33]. Many studies have confirmed that many NAC genes play crucial roles in the regulation of plant tolerance to drought.…”
Section: Introductionmentioning
confidence: 99%